(untitled) (Raparin Journal of Humanities (RJH), 2024)
Marriage in Islam is a contract that has great purposes, and its goal is noble, as it is the path of chastity, and the way of procreation, and since the family is the nucleus of the nation and its foundation Islam has taken great care of it, preserving its entity and making it coherent and homogeneous. The marriage of a Muslim to a woman of the people of the Book in Islam has a special importance, since marriage between people of different religions is not permitted. And if the expression is correct, mixed marriage, except for Islam, which permitted marriage of people of the Book, and thus establishes a basis for interaction between human beings and that all people are brothers who deal on the basis of humanity, no matter how different their religions, languages and colors are. They are brothers in humanity, which means acquaintance and cooperation. The Almighty said (O mankind! We have created you from a male and a female, and made you into nations and tribes, that you may know one another. Verily, the most honorable of you with Allah is that (believer) who has At-Taqwâ. ( Al-Hujraat13) And the relationship between Muslims and people of other religions is based on foundations governed by the rules of interests and harms that are linked to the reality that varies from time to time. The condition of Muslims is calculated as strength and weakness. the first era, so God permitted marriage to women of the Book, and some of the Companions of them got married, such as Othman, Hudhaifa, and others, then Umar (may God be pleased with him) forbade it and asked them to divorce them. Then Ibn Omar (may God be pleased with him) forbade it. It appears from that that he singled out the permissibility in one case rather than another, and this indicates that the ruling in the matter is linked to the circumstances of the era and is influenced by what the Muslims are upon. And in the case of the writings and the surrounding circumstances, all of this makes researching the issue, investigating the opinions of the jurists on it, and knowing the different points of view regarding it a matter required. Especially when there are many religions and sects that non-Muslims condemn. All of this makes studying the issue a picture that is consistent with reality and extracting an opinion that is consistent with reality is a scientific necessity. This research comes to study this topic and its scientific material was distributed into three demands and a conclusion in which we summarized the most important results and recommendations.